2018
DOI: 10.1111/jce.13494
|View full text |Cite|
|
Sign up to set email alerts
|

Challenges and limitations in the diagnosis of atrioesophageal fistula

Abstract: The diagnosis of AEF remains challenging. Clinicians should be aware of the limitations in the yield of CT chest, the variety of major abnormalities reported, the need for repeat testing, unique brain imaging findings, and the importance of positive blood cultures and raised inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Based on a systematic review, among 11 patients, major abnormalities were detected in 10 (91%) patients on repeat CT chest scans performed six days following the initial scan. 10 Once an EF diagnosis is suspected, endoscopy is not safe to perform since insufflation can lead to systemic air emboli.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a systematic review, among 11 patients, major abnormalities were detected in 10 (91%) patients on repeat CT chest scans performed six days following the initial scan. 10 Once an EF diagnosis is suspected, endoscopy is not safe to perform since insufflation can lead to systemic air emboli.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Similarly, another systematic review found a clear diagnosis of AEF was made in 35% of cases with thoracic CT modality. 8 As such, in cases with high suspicion, surgeons sometimes may have to commit to a surgery without a confirmed diagnosis of fistula, especially since early surgical repair is crucial, and the mortality without treatment is 100%. 9 There have been reported cases of endoscopic esophageal stent placement for the management of AEF; however, most of these cases have shown much worse outcome than compared with surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Ha et al performed an extensive literature review of reported cases and found that the only method of certainty is the presence of blood culture positivity, particularly with respect to streptococcal species. 8 Computed tomography imaging was successfully diagnostic in only one-third of cases.…”
Section: Trouble In Paradisementioning
confidence: 99%